2020
DOI: 10.1101/2020.12.16.20245191
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of housing conditions on changes in youth’s mental health following the initial national COVID-19 lockdown: A cohort study

Abstract: BackgroundYouth’s mental health has on average declined initially during the pandemic and few studies have investigated whether these declines were dependent on housing conditions.MethodsWe used data from 7445 youth from the Danish National Birth Cohort (DNBC), collected at participants’ 18th year of life and subsequently three weeks into the initial national lockdown (April 2020). We examined associations between housing conditions (access to outdoor spaces, urbanicity, household density, and household compos… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
2
3
0
1
Order By: Relevance
“…Both Syrian and Lebanese adolescents living in overcrowded and substandard housing associated their homes with a loss of pride, a feeling of neglect and a lack of privacy. This accords with Groot et al.’s finding that poor housing conditions such as high-density households were associated with the onset of Low Quality of Life score amongst adolescents ( Groot et al., 2022 ). Maha and other adolescents in this study valued solitary space for self-reflection and contemplation, which they said was important for their mental health.…”
Section: Discussionsupporting
confidence: 90%
“…Both Syrian and Lebanese adolescents living in overcrowded and substandard housing associated their homes with a loss of pride, a feeling of neglect and a lack of privacy. This accords with Groot et al.’s finding that poor housing conditions such as high-density households were associated with the onset of Low Quality of Life score amongst adolescents ( Groot et al., 2022 ). Maha and other adolescents in this study valued solitary space for self-reflection and contemplation, which they said was important for their mental health.…”
Section: Discussionsupporting
confidence: 90%
“…balcony, garden, or yard) compared to none, may lower levels of anxiety during a lockdown. Consistently, results from our previous study among young people in Denmark have shown that individuals without access to outdoor spaces experienced greater decline in well-being during the COVID-19 pandemic 21 . Therefore, housing and urban design strategies should ensure access to outdoor spaces for all 56 .…”
Section: Discussionsupporting
confidence: 88%
“…Increased house surface area was positively associated with wellbeing in a French study 18 and a high prevalence of moderate-to-severe depressive symptoms was observed amongst Italian students living in dwellings < 60 m 2 19 . Furthermore, living alone was reported to be associated with greater loneliness 20 , 21 . To our knowledge, no previous studies have assessed the role of housing conditions during lockdowns on multiple mental health indicators in a multi-cohort study across Europe.…”
Section: Introductionmentioning
confidence: 99%
“…(2020) , Flentje et al. (2020) , Giuntella, 2020 , Groot, 2020 , Hafstad, 2020 , Hajdúk et al. (2020) , Hamm et al.…”
Section: Articles Included In the Review And Not Cited In Textunclassified